Culture shock (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
Annotation: Culture shock is a common phenomenon experienced by individuals who find themselves in a new and unfamiliar cultural environment. It can be a challenging and disorienting experience, as individuals may feel overwhelmed by the differences in customs, traditions, language, and social norms.